Fertility preservation and monitoring in adult patients diagnosed with lymphoma: consensus-based practical recommendations by the Fondazione Italiana Linfomi & Società Italiana della Riproduzione Umana - Minoia, Carla; Viviani, Simonetta; Silvestris, Erica; Palini, Simone; Parissone, Francesca; De Palma, Giuseppe; Fedina, Anna; Cormio, Gennaro; Guarini, Attilio; Gini, Guido; Montano, Luigi; Merli, Francesco; et al. (Frontiers in Oncology, 2023)
Fertility preservation (FP) and monitoring has considerable relevance in the multidisciplinary approach to cancer patients. In these consensus-based practical recommendations, the scientific societies Fondazione Italiana Linfomi (FIL) and Società Italiana della Riproduzione Umana (SIRU) reviewed the main aspects and identified the optimal paths which aim to preserve and monitor fertility in patients diagnosed with lymphoma at the different phases of the disease and during long-term survivorship.For the Panel, eleven experts were selected for their expertise in research and clinical practice on onco-fertility and lymphoma. The Panel's activity was supervised by a chairman. A series of rank-ordering key questions were proposed according to their clinical relevance and discussed among the Panel, focusing on patients diagnosed with non-Hodgkin's lymphomas and Hodgkin lymphoma. Agreement among all the Panelists on the content and terminology of the statements was evaluated by a web-based questionnaire according to the Delphi methodology. Two rounds of Delphi were completed in order to provide the maximum agreement. All statements were newly discussed in a round robin way and confirmed for the drafting of the final recommendations. These recommendations would be useful for onco-hematologists, gynecologists, urologists, and general practice physicians who take care of young lymphoma patients to guarantee an evidence-based oncofertility assessment and treatment during the oncologic pathway.